KOLABORASI GURU PAI DAN ORANG TUA DALAM MENGATASI PERILAKU TABARRUJ PADA SISWA DI MAS ISLAMIYAH GUNTING SAGA KABUPATEN LABUHANBATU UTARA - Silaen, Irma; Mardianto, Mardianto; Darlis, Ahmad (IAIN Bone, 2024)
This research is motivated by the problem of tabarruj behavior of students. Collaboration will strengthen students' awareness of the negative impacts of tabarruj behavior and strengthen understanding that Islam highly honors women by requiring women to cover their genitals perfectly. This type of research is descriptive qualitative research. The data collection methods used are observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and data conclusions. The data sources for this research informants are the principal, Islamic Religious Education teachers, and parents of students at MAS Islamiyah Gunting Saga, North Labuhanbatu Regency. The results of the study obtained related to the form of collaboration between Islamic Religious Education teachers and parents in overcoming tabarruj behavior in students are holding meetings and writing to parents of students, direct communication at school and indirectly through social media with parents of students, parents controlling children's behavior from home and Islamic Religious Education teachers controlling student behavior at schoolKeywords: Collaboration, Tabarruj, Students